2019
DOI: 10.1155/2019/8201096
|View full text |Cite
|
Sign up to set email alerts
|

Serum Creatinine Level and APACHE-II Score within 24 h of Admission Are Effective for Predicting Persistent Organ Failure in Acute Pancreatitis

Abstract: Aim. The present study was aimed at comparing serum markers and APACHE-II score to predict persistent organ failure (POF) in early acute pancreatitis (AP). Methods. In this retrospective study, data from 6024 patients with AP were included within 24 h of their admission. Serum levels of urea nitrogen (BUN), creatinine, glucose, and hematocrit and APACHE-II score were analyzed for patients with AP. We employed the area under the receiver operating characteristic (ROC) curve (AUC), sensitivity, and specificity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 26 publications
2
16
0
Order By: Relevance
“…Elevated SCR as an indicator of acute kidney injury (AKI) was associated with pancreatic necrosis, organ failure and mortality in AP as well[22, 23]. Early change especially in the first 24 hours after admission in SCR level was an effective predictor of disease severity in AP[24].…”
Section: Discussionmentioning
confidence: 99%
“…Elevated SCR as an indicator of acute kidney injury (AKI) was associated with pancreatic necrosis, organ failure and mortality in AP as well[22, 23]. Early change especially in the first 24 hours after admission in SCR level was an effective predictor of disease severity in AP[24].…”
Section: Discussionmentioning
confidence: 99%
“…The study presented is compatible with previous studies on toxic substances. Previous studies have reported that changes in the serum creatinine level are indicators of toxicity and mortality (Muddana et al 2009, Liew et al 2019, 2015, Santos Silva et al 2018, Wan et al 2019. In one study, the serum creatinine level at 48 h was considered an extremely accurate determinant of pancreatic necrosis (Wan et al 2019).…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies have reported that changes in the serum creatinine level are indicators of toxicity and mortality (Muddana et al 2009, Liew et al 2019, 2015, Santos Silva et al 2018, Wan et al 2019. In one study, the serum creatinine level at 48 h was considered an extremely accurate determinant of pancreatic necrosis (Wan et al 2019). The presently reported study supports this situation because the creatinine level increased significantly after 48 h. When the kidney or liver is damaged, the urea level may begin to rise (Llopis-Lorente et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, twelve variables including age, ALT, total bilirubin, CK-Mb, PT, WBC, amylase, total calcium, creatinine, HCT, lactate, and lipase which were identified to be significant difference by univariate analysis were set as the input layers, and the most important four variables including total bilirubin, amylase, ALT and creatine were identified, which also were reported in other studies. Evidence showed that the levels of total bilirubin and ALT were significantly higher in AP patients with a Ranson score ≥3 [ 23 ], and early elevated creatinine within 24 hours after admission was a good predictor of fatal outcomes in AP patients [ 24 ]. Serum level of amylase was not only for AP diagnosis but also associated with severity and prognosis of AP [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%